The discipline of leisure : embodying cultures of 'recreation' - Coleman, Simon, 1963-; Kohn, Tamara (Social identities ;, 2007)
The burgeoning social scientific study of tourism has emphasized the effects of the post-industrial economy on travel and place. However, this volume takes some of these issues into a different area of leisure: the spare-time carved out by people as part of their everyday lives - time that is much more intimately juxtaposed with the pressures and influences of work life, and which often involves specific bodily practices associated with hobbies and sports. An important focus of the book is the body as a site of identity formation, experience, and disciplined recreation of the self. Contributor.